AYAT AL - QUR'AN TENTANG MANAJEMEN KESISWAAN DAN PENERAPANNYA DI SMK BABUNNAJAH - Hidayat, Yayat Samsul (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2023)
Management is the effective use of resources to achieve goals in education. In the context of student affairs, student affairs management is the structuring and organization of activities related to students, starting from the entry to the exit of these students from one school. The objectives of this study are: (1) to explore information about the implementation of student management in SMK Babunnajah Pandeglang. (2). Exploring information on efforts made in an effort to improve student management at SMK Babunnajah. In carrying out student management, it is carried out by forming a management plan, this management starts from the process of students entering the school until the students graduate by carrying out stages.1. Student management planning in schools such as schools record the size of the school, class size, number of classes, student and teacher staffing needs, and the ratio of the number of students and teachers. 2. coaching (student council and extracurricular activities), providing schedules and school regulations. 3 Monitoring and Evaluation of School Student Management.